Force time measures of beginning and skilled skateboarders performing an ollie - Walsh, M.; Creekmur, C.; Wojcik, J. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
It was reported (US today) that in 2001 more American youth participated in skateboarding than baseball. The growing popularity of the urban skating in recent years has been a factor in the transformation of the sport and the tricks that are performed. In the early days of skateboarding aerials and various vertical manoeuvres made up the majority of the tricks performed. With the increase in urban skating, Ollie based tricks have become an integral part of many competitions. An Ollie is a manoeuvre in which the skater jumps up in the air and as a result of torques applied to the skateboard the skateboard rises up in the air under the feet of the skater. Although a large number of people participate in skateboarding there is little research outlining the mechanics of basic skateboarding tricks.